Response of suspended sediment dynamics to human activities in the transitional zone between Changjiang Estuary and Hangzhou Bay - Xie, Dongfeng; Chen, Yuwen; Pan, Cunhong; Zhang, Shenyang; Wei, Wen; Wang, Zheng Bing; Gu, Jiali; Duan, Wenyi (Frontiers in Marine Science, 2024)
The Changjiang Estuary and Hangzhou Bay system has experienced river damming and estuarine engineering in the last decades. However, few studies focused on the shifts in its sediment dynamics due to such human activities. In this study multi-decadal development of sediment dynamics in the transitional zone of the two large estuaries was analyzed, based on the synchronous hydrographic data in the winter of 2023, 2014 and 1983. The results revealed significant changes in regional hydrodynamics and suspended sediment transport, despite the continuous good correlations between the current velocity, suspended sediment concentration (SSC), water/sediment fluxes and tidal range. Specifically, the current velocity has been decreased by 8 - 21% after 2014, mainly due to the land reclamation (implemented around 2016) with several groins stretching into deep water and altering alongshore hydrodynamics. The SSC has decreased further by 29 - 38% in addition to the significant decrease during 1983 - 2014. The SSC changes are related to the combination of river damming which induced sediment load reduction and land reclamation which enclosed a large amount of sediment. Furthermore, the sediment transport from Changjiang Estuary to Hangzhou Bay decreased by 36% - 53%, explaining the observed bed erosion in the northern bay mouth in recent years. The findings are also relevant for studies on sediment dynamics in other large estuaries worldwide.